2014
DOI: 10.1111/1556-4029.12471
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Meteorological Conditions and Homicide, Suicide, Rage, and Psychiatric Hospitalization

Abstract: This study focuses on the relationship between the incidence of homicide, rage, suicide, and psychiatric hospitalization as violent behaviors with temperature, humidity, and air pressure as specific meteorological variables in the city of Mashhad, in the northeast of Iran. The data were obtained from Iran Meteorological Organization, official registry of Legal Medicine Organization and the local psychiatric hospital, March 2009 to Feb 2010 daily and were analyzed with SPSS-14 using Pearson correlation coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 61 publications
0
12
0
2
Order By: Relevance
“…The suicidal rate might have been influenced by climatic and seasonal triggering factors . In the previous study, 4918 suicidal cases (3099 male, 1819 female) were investigated in Budapest in connection with climatic data, such as daily maximum, minimum temperature, and air humidity.…”
Section: Discussionmentioning
confidence: 99%
“…The suicidal rate might have been influenced by climatic and seasonal triggering factors . In the previous study, 4918 suicidal cases (3099 male, 1819 female) were investigated in Budapest in connection with climatic data, such as daily maximum, minimum temperature, and air humidity.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicate that ‘violent crime’ as a broad category (often including homicide, assault, burglary, domestic violence and/or rape) may be positively associated with ambient temperature [1, 4, 5, 821], but evidence on the relationship between temperature and homicide specifically is more limited [3, 11, 1317, 22, 23]. A recent paper [24] on the links between heat and homicide reviewed 16 studies, noting that nine reported a significant positive association whereas the others reported positive but non-significant associations.…”
Section: Introductionmentioning
confidence: 99%
“…20 Talaie et al discussed the relationship between homicide, suicide and hospitalization of psychiatric patients in Mashhad according to climatic factors, and they found a strong relationship between violence and hospitalization of mental patients with a daily average temperature, minimum and maximum relative humidity, and minimum and maximum daily atmospheric pressure. 21 Rosenthal et al reported that clinical depression occurs regularly during the winter months and decrease during spring and summer. They also noticed some related high range of changes in behavioral and physiological of people, including decreased physical activity, change in appetite, increased drowsiness, reducing of social interactions and increased excitability to winter.…”
Section: Discussionmentioning
confidence: 99%